Proceedings of the 2017 ACM SIGSAC Conference on Computer and Communications Security 2017
DOI: 10.1145/3133956.3134051
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic, Stash-Free Write-Only ORAM

Abstract: Write-Only Oblivious RAM (WoORAM) protocols provide privacy by encrypting the contents of data and also hiding the pattern of write operations over that data. WoORAMs provide better privacy than plain encryption and better performance than more general ORAM schemes (which hide both writing and reading access patterns), and the write-oblivious setting has been applied to important applications of cloud storage synchronization and encrypted hidden volumes. In this paper, we introduce an entirely new technique fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…In fact, the reduction in I/O requests makes rORAM faster than Path ORAM even for SSDs (around 30x) and network block devices (around 10x). As noted previously [36], ensuring locality of accesses improves performance on SSDs while the reduced number of round-trips required to fetch all blocks in a range makes rORAM faster for network block devices.…”
Section: Query Access Timementioning
confidence: 74%
See 4 more Smart Citations
“…In fact, the reduction in I/O requests makes rORAM faster than Path ORAM even for SSDs (around 30x) and network block devices (around 10x). As noted previously [36], ensuring locality of accesses improves performance on SSDs while the reduced number of round-trips required to fetch all blocks in a range makes rORAM faster for network block devices.…”
Section: Query Access Timementioning
confidence: 74%
“…First introduced by Blass et al [11] in the context of protecting hidden volumes, a randomized procedure was used to achieve obliviousness. Later, Roche et al [36] showed that writeobliviousness can be achieved with deterministic, sequential writing patterns. However, the data locality of reads was not evaluated, and depends largely on the write pattern itself.…”
Section: Prior Workmentioning
confidence: 99%
See 3 more Smart Citations